Disease activity and joint damage progression in early rheumatoid arthritis: relation to IgG, IgA, and IgM rheumatoid factor. Issue 11 (November 1990) - Eberhardt, K B; Truedsson, L; Pettersson, H; Svensson, B; Stigsson, L; Eberhardt, J L; Wollheim, F A
Abstract : The clinical and biochemical correlations with joint damage progression over two years in a consecutive group of 68 patients with rheumatoid arthritis with disease duration of less than two years are reported. Joint damage was assessed with Larsen's severity scale and a measure of change in progression rate constructed. Initial haemoglobin concentration, Ritchie index, and Waaler-Rose titre in combination accounted for one third of the variance in joint damage progression. Rheumatoid factor (RF) concentrations were followed with enzyme linked immunosorbent assays (ELISAs) for IgG RF, IgA RF, and IgM RF. The RF concentrations, except IgG RF, decreased with time; significant correlations between RFs and disease activity were few and barely clinically useful. After two years IgG RF correlated significantly with a radiological score if early non-erosive changes were omitted. All RFs tended to correlate better with this radiological score at all three observation points. Analyses of the change in progression rate indicated a time delay between development of radiographic changes and increase of IgG RF. These results suggest an indirect relation between RFs and joint damage. Clinical and biochemical improvements in early RA occur despite joint damage progression, and conventional markers have insufficient predictive value.